Comparative Studies on Production of Cell Wall-Degrading Hydrolases by Trichoderma reesei and T. viride in Submerged and Solid-State Cultivations (Bangladesh Journal of Microbiology, 2008)
Lignocellulose-degrading organisms have been used for the conversion of lignocellulosic materials into soluble sugars or solvents in several biotechnological and industrial applications. Complete degradation of complex highly structured lignocellosics requires a concerted action of a wide array hydrolytic enzymes. In this study, two newly isolated fungi, Trichoderma reesei and T. viride, were examined for their ability to produce cellulolytic, xylanolytic and pectinolytic enzymes in submerged and solid-state fermentations. The fungi produced appreciable amounts of the enzymes when grown on potentially low cost lignocellulosic agricultural residues like wheat bran, sugar cane bagasse and corncobs. T. viride seems to be superior to T. reesei with respect to enzyme productions both in submerged and solid-state cultivations. There was a distinct influence of culture methods on the production of the enzymes by the fungi. The enzyme productions were higher in solid-state fermentations than in submerged fermentations. However, taking into consideration of enzyme yields per gram substrate, it was found that the yields were many-fold higher in submerged cultures than in solid-state fermentations. The recovery of the enzymes from fermented slurries in solidstate fermentations was enhanced by using non-ionic surfactant Tween 80 as leaching agent. The enzymes produced by the fungi displayed optimum activities at pH range between 4.5 and 5.5, and at temperatures between 50 and 55°C. The fungi merit further attention as potential sources of industrial enzymes, as they exhibited some excellent properties including the ability to synthesize a wide array of hydrolytic enzymes while grown on cheap and readily available lignocellulosic residues. Keywords: Lignocellulosics, cellulase, xylanase, pectinase, Trichoderma reesei, Trichoderma viride, submerged culture, solid-state fermentationDOI: http://dx.doi.org/10.3329/bjm.v23i2.882 Bangladesh J Microbiol, Volume 23, Number 2, December 2006, pp 149-155